EFEKTIVITAS PENGGUNAAN GAME EDUKASI GCOMPRIS DALAM MENINGKATKAN KEMAMPUAN BERNALAR KRITIS PADA MATERI PEMBAGIAN SISWA KELAS IV SD - Habib Abdurrasyid; Ema Butsi Prihastari; Elinda Rizkasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of students’ critical thinking skills in solving mathematical word problems, particularly in division material. This study aims to determine the effectiveness of the GCompris educational game in improving fourth-grade elementary students' critical thinking skills. This research employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest model. The subjects were 18 fourth-grade students of SDIT Bina Insani in the 2024/2025 academic year. Data collection techniques included tests, observations, interviews, and documentation. The instrument consisted of essay questions that had been tested for validity and reliability. Data were analyzed using normality tests and paired sample t-tests. The results showed that the mean pretest score of 39.7 increased to 73.3 in the posttest. The hypothesis test indicated a significance value of 0.000 < 0.05, meaning there was a significant difference before and after the treatment. Thus, the use of the GCompris educational game is effective in improving students' critical thinking skills in mathematics learning.